Radical right and anti-vax protests between movements and parties: a comparative study - Caiani, Manuela; Susanszky, Pal; Saridakis, Nikos (Acta politica, 2025)
Mobilisations opposed to vaccinations and other Covid-19-related measures have dominated the protest arena in the recent years of the pandemic. Radical right collective actors, whether newly emerging or revitalised, have successfully shaped public discourses and gained significant roles on the streets and in party politics. This paper analyses the radical right (RR) mobilisation that takes place in response to the pandemic, looking at the main actors , demands and strategies behind protest events, and paying particular attention to the relationship between movements and parties . The analysis focusses on Italy and Hungary, two European countries characterised by favourable political opportunities for radical right mobilisation in recent years. The argument is that the pandemic offered a new window of opportunities for the empowerment of (new and old) radical right collective actors, leading, however, to different outcomes in terms of ‘movement–parties’ relations (or ‘movement–parties’ formation). The article draws on a mixed method approach including a protest event analysis based on newspapers and police records (2021–2022), comprising more than 300 events, and 30 in-depth interviews with radical right and anti-vax activists and leaders in both countries. The findings highlight that while health-related demands are the most important issues in both countries, the outcomes of such protests are different, both in terms of the intensity of radical right mobilisation (including violence) and in the movement–party relations . In the Italian case, the protest against vaccines gives birth to a strict division of labour or ‘conflict’ between RR movements (which remained the main actors of the street protest) and political parties (in institutions), while in Hungary the two sides are characterised by ‘cooperation’. These results demonstrate that in the two analysed countries, anti-vax and Covid-19-related protests have different impacts on national politics and the conflict arena, which require investigation of movement–party relations to be fully grasped.